Final Monitoring and Evaluation Report on Socio-Technical Innovation Bundles for Gender Equality and Climate Resilience in Kenya - Ayuya, Oscar Ingasia; Jong, Arnold Otieno; Lutomia, Cosmas Kweyu; Nchanji, Eileen Bogweh; Waswa, Boaz Shaban; Ooro, Patrick; Muriithi, Catherine; Njiru, Emerita (Bioversity International and the International Center for Tropical Agriculture, 2024)
Inequalities are prevalent in agri-food systems in sub-Saharan Africa due to multifaceted challenges. Unequal decision making power, access to resources, and land ownership contribute to the inequalities. Climate change, which disproportionately negatively affects women, exacerbates existing inequalities in agri-food systems. Existing policy and governance systems have not adequately addressed the inequalities. Socio-technical innovations (STIBs) have the potential to address climate change and challenge sociocultural norms that create inequalities. The CGIAR Gender Equality initiative (HER+: Harnessing Equality for Resilience in the Agrifood System) collaborates with CGIAR Diversification in East and Southern Africa to contribute to climate resilience and women’s empowerment in Kenya through the STIBs approach. Two studies – choice experiment and qualitative monitoring and evaluation – were conducted in three HER+ learning labs in Kenya to assess farmers’ preferences for specific components of socio-technical innovation bundles and measure the impact of HER+ and Diversification in East and Southern Africa initiatives on agricultural productivity, climate resilience, and women's empowerment. Adoption of farmer preferred STIBs – certified seeds, CA/CSA practices, intercropping, extension services, farmer-to -armer extension, and access to financial services – led to high productivity, resilience, and empowerment outcomes.